Karyotypes of water scavenger beetles (Coleoptera: Hydrophilidae): new data and review of published records. Issue 3 (20th October 2020) - Angus, Robert B; Sadílek, David; Shaarawi, Fatma; Dollimore, Hayley; Liu, Hsing-Che; Seidel, Matthias; Sýkora, Vít; Fikáček, Martin
Abstract: This study summarizes available data on karyotypes of water scavenger beetles (Coleoptera: Hydrophiloidea: Hydrophilidae), based on newly acquired data of 23 genera and 64 species. We combine these data with previously published data, which we review. In total, karyotypes are available for 33 genera and 95 species, covering all subfamilies and tribes. Available data indicate that most groups of the Hydrophilidae are diploid and sexually reproducing, with XY (♂) and XX (♀) sex chromosomes; the Y chromosome is always minute and does not recombine with X during meiosis. Exceptions are known in Anacaena, with parthenogenetic diploid or triploid populations in some species and sex chromosomes fused with autosomes in others. The diploid number of chromosomes is 2 n = 18 in the subfamilies Acidocerinae, Chaetarthriinae, Enochrinae and Hydrophilinae. Variations are known in species of Anacaena and Berosus (both usually with 2 n = 18) and in Hydrochara and Hydrophilus with an increased number of chromosomes (2 n = 30). The number of chromosomes is increased in the subfamily Cylominae (2 n = 24–30) and in all subclades of the subfamily Sphaeridiinae (2 n = 22–32). We summarize protocols for obtaining chromosome slides used for this study and provide step-by-step guidelines to facilitate future cytogenetic studies.